2015
DOI: 10.1016/s0140-6736(15)60733-4
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired pneumonia

Abstract: Community-acquired pneumonia causes great mortality and morbidity and high costs worldwide. Empirical selection of antibiotic treatment is the cornerstone of management of patients with pneumonia. To reduce the misuse of antibiotics, antibiotic resistance, and side-effects, an empirical, effective, and individualised antibiotic treatment is needed. Follow-up after the start of antibiotic treatment is also important, and management should include early shifts to oral antibiotics, stewardship according to the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
336
1
54

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(403 citation statements)
references
References 149 publications
(144 reference statements)
12
336
1
54
Order By: Relevance
“…Lower respiratory tract infections cost the healthcare system more than 10 billion dollars annually in the United States (1,2). Community-acquired pneumonia (CAP) and influenza infections together are the fourth most prevalent cause of death worldwide (3).…”
Section: Introductionmentioning
confidence: 99%
“…Lower respiratory tract infections cost the healthcare system more than 10 billion dollars annually in the United States (1,2). Community-acquired pneumonia (CAP) and influenza infections together are the fourth most prevalent cause of death worldwide (3).…”
Section: Introductionmentioning
confidence: 99%
“…Much has been written regarding what constitutes appropriate and/or optimal antibiotic treatment, and this has been extensively reviewed elsewhere (1,(7)(8)(9). However, while it is well recognised that inappropriate initial antibiotic therapy is associated with a worse outcome, it is also noted that even in the setting of appropriate initial antibiotic treatment, many patients still die (10).…”
Section: Review Articlementioning
confidence: 99%
“…However, while it is well recognised that inappropriate initial antibiotic therapy is associated with a worse outcome, it is also noted that even in the setting of appropriate initial antibiotic treatment, many patients still die (10). This has resulted in considerable interest in the potential role of adjunctive, anti-inflammatory therapies in the management of patients with CAP, particularly among the more seriously ill patients (1,(7)(8)(9)11,12). Shindo and colleagues recently studied risk factors for 30-day mortality in patients with CAP who had received appropriate antibiotic therapy, with the aim of trying to identify patients who were most likely to benefit from adjunctive therapy (10).…”
Section: Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…78 For example, despite the victory in the constitutional court noted above (on the teaching of Tatar and Russian 'in equal measure'), in practice the amount of teaching of, and through the medium of, Tatar, has incrementally decreased since the 2000s. 79 The shrinking of territorial autonomy and the resulting limitations in the promotion of Tatar interests indicate a tendency for law and policy for the protection of minority rights to be treated as having primarily a symbolic, rather than an instrumental, role. 80 For example, in relation to language legislation, it has been suggested that relevant legal provisions -such as those declaring regional languages co-official alongside Russian at the level of republicsnever intended to be fully implemented, but merely to fulfil a symbolic function.…”
Section: Tatarstanmentioning
confidence: 99%